A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages the particular services which the joint authority will itself administer, but the whole range of services of which the National Health Service will be composed. Unless provision is made for the interlocking of the various parts of the service it cannot possess the coherence and unity of purpose which are essential features of the Government's proposals. The preparation of a comprehensive plan of this kind is a function appropriate to the joint authority and not to its constituent members. The plan will be submitted to the Minister for approval, and when approved it will determine how the needs, of the area in terms of general practice, hospitals, consultants, clinics and all other necessary services are to be met and will define, subject to the principles laid down, the responsibilities of the various authorities. The plan will be open to amendment at any time by the same procedure. Both in its preparation and in its amendment the authority will fully consult local professional and expert opinion, through the medium of a Local Health Services Council. Local Health Services Councils Expert guidance is no less needed locally than it is at the centre. To meet the local need the Government propose that there shall be established, for the area of every joint authority, a Local Health Services Council. These Councils will be the local counterparts of the Central Health Services Council. Their constitution will call for more detailed consideration later but, provided that all the professional interests are fairly represented, there is no reason why the pattern should be precisely uniform everywhere — and the matter might be dealt with by local schemes approved by the Minister. The Councils will be able not only to advise on matters referred to them by the joint authority or other local authorities in the area, but also to initiate advice on any matters within their expert province on which they think it right to do so. They will be free, if they wish, to submit their views and advice not only to the joint authority or, on matters affecting other local authorities in the area, to those authorities, but also to the Minister. The joint authority will be required to consult the Council on the area plan for the health service before it is submitted to the Alinister, and on any subsequent material alterations or additions to the plan. VII THE SERVICE IN SCOTLAND Certain differences essential The scope and purpose of the National Health Service will be the same in Scotland as it is in England and Wales, but the administrative structure of the service in the two countries cannot be identical. 23 36/H24/41